PENGARUH KEBIJAKAN INVESTASI, KEBIJAKAN HUTANG DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia yang terdaftar di Bursa Efek Indonesia (BEI) Periode 2014-2018) - Mohammad Andri Dwi Aprianto; Ninnasi Muttaqiin; Mohamad Yusak Anshori (Ecopreneur.12, 2020)
This study aims to examine the effect of investment policy, debt policy, and dividend policy on firm value. The dependent variable in this study is the value of the company with the Price to Book Value (PBV) indicator. The independent variables in this study are investment policies with Price Earning Ratio (PER) indicators, debt policies with Debt to Equity Ratio (DER) indicators, dividend policies with Dividend Payout Ratio (DPR) indicators. This study uses secondary data, the data obtained in the form of annual reports of manufacturing companies, basic and chemical industry sectors listed on the Stock Exchange in the 2014-2018 period. The sample in this study amounted to 13 companies. This study uses a purposive sampling method and the method of analyzing data in this study uses SPSS 22 for windows. The analysis showed that only partially investment policy (PER) had a positive and significant effect on company value (PBV), while debt policy (DER) and dividend policy (DPR) had a non-significant positive effect on firm value (PBV). Simultaneous test results of investment policy variables (PER), debt policy (DER), and dividend policy (DPR) have a significant positive effect on firm value (PBV).